A coenological and biogeographical survey on the acidophilous and chionophilous high-altitude grasslands of the Apennines (Peninsular Italy). - Romeo Di Pietro; Massimo Terzi; Paola Fortini (Dipartimento di Biologia Ambientale Università sapienza di Roma, 2016)
The high-altitude grasslands of the central Apennines were the topic of the first phytosociological studies on the Peninsular Italy mountains and were performed in the first decade of the 60ies. The majority of the names of the syntaxa used in that period were drown up from the syntaxonomical frameworks already known for the Alps and the Balkans. Subsequently new endemic associations and alliances were proposed. The new alliances linked to the vegetation of dry environments such as the limestone ridges, screes and cliffs (namely Seslerion apenninae, Festucion dimorphae, Saxifragion lingulatae) were characterized by a strong Apennines endemic component whereas the acidophilous grasslands showed a higher number of mesophilous species shared with the Alps and the C-Europe. The acidophilous grasslands of the northern Apennines, majorly developed on siliceous substrates and rich in boreal and arctic-alpine species, were immediately classified in the Nardion strictae. Different was the situation of the central and the southern Apennines, being these sectors almost completely composed of limestone substrates and majorly influenced by the Mediterranean climate. This led Bonin to propose the new endemic alliance Ranunculo-Nardion, in a first moment solely for the high-altitude acidophilous grasslands of the southern Apennines and subsequently for those of the central Apennines too. This proposal was shared by the majority of the authors who published later on this topic. The chionophilous and sub-acidophilous grassland communities occurring between the Seslerion apenninae and the Ranunculo-Nardion, however, remained for a long period in an undefined syntaxonomical position and were classified, depending on the case, as the “mesophilous fringe” of the Seslerion apenninae, the “xerophilous fringe” of the Ranunculo-Nardion, or in new endemic alliances (Caricion kitaibelianae, Festucion violaceae, and Festucion macratherae) created especially for them. The aim of this paper is to clarify the coenological, syntaxonomical and ...